Children's food during the pandemic and the difficulties of the responsible (Research, Society and Development, 2021)
In this paper, we will address the difficulty faced by families currently facing the COVID-19 scenario for healthy infant feeding with variety. Facing financial difficulties and through the new normal with HOME OFFICE work and having children at home, so that in addition to the demand for work, it is necessary to prepare the food for your children.